The business model innovation process : preparation, organization and management - Taran, Yariv, 1972-; Boer, Harry, 1955-; Nielsen, Christian (Routledge studies in innovation, organization and technology., 2022)
"Business Model Innovation Process: Preparation, Organization and Management examines a range of critical questions that merit thoughtful interdisciplinary consideration, such as: Why do business models, and their innovation in particular, matter today? How can the process of business model innovation be understood, organized and managed adequately under increasingly volatile, uncertain, complex and ambiguous technological, business and geo-political conditions? What should decision-making and risk-management look like under these conditions, with managers whose rationality is bounded? The book offers a detailed account of the relatively unknown process of business model innovation by looking into the intersection of strategic, operations and innovation management, organizational design, decision-making and performance management. In doing so, this book addresses fundamental issues, and introduces new ideas and theoretical perspectives. In envisioning and thinking about various potential scenarios of business model innovation and understanding how to organize for each of these under different conditions, the book provides original arguments and suggestions for practitioners. For that purpose, the book also offers many compelling real-life examples of business models and their innovation. Combining theory and practice, this book is an essential read for researchers and academics of business model innovation, as well as strategic management, digital transformation, innovation management and organizational change. It will also be of direct interest to practitioners and business leaders seeking new perspectives to increase their competitive advantage"--